Evaluation of preventing chemotherapy induced oral mucositis project in patients with cancer of the female reproductive system at Maharaj Nakorn Chiang Mai Hospital, Thailand - Phianmongkhol Y. (2014)
Oral mucositis is an important and common complication among female patients who have cancer of the reproductive system receiving chemotherapy. This study aimed to evaluate the prevention of chemotherapy-induced oral mucositis project in female reproductive system cancer patients at Maharaj Nakorn Chiang Mai Hospital. The clinical practice guidelines evaluation model of the Registered Nurses Association of Ontario (RNAO, 2002) was used as a framework. The subjects included 14 nurses and practical nurses, and 404 patient reports. Data were collected by using of two forms developed by the researcher; the nurses' opinion form about the project's implementation and a mucositis form. Data analysis was conducted using frequency, percentage, and mean. The findings showed that 92.9 % of the subjects reported that they could consistently follow the clinical practice guidelines. All of them (100.00 %) agreed that the clinical practice guidelines were easily to follow, convenient to use, had good outcome, reduced nursing time, and were satisfied with this project. After the project's implementation, it was found that mucositis was reduced from 22.0 % to 9.9 %. The results of this study confirm that with the prevention chemotherapy-induced oral mucositis project for female reproductive system cancer patients, care is more efficient. These results could be extended for use in other similar settings.